Transportasi Sistem Informasi Akuntansi Berbasis Cloud Serta Dampaknya Terhadap Efisiensi Operasional dan Keberlanjutan Bisnis - Dewi Zulvani; Jessica Dara Novita; Lusi Nur'Aini; Novemy Triyandari Nugroho (Proceedings Law, Accounting, Business, Economics and Language, 2025)
The transformation of Accounting Information Systems (AIS) based on cloud technology is increasingly relevant in supporting operational efficiency and business sustainability in the digital era. This article aims to review the literature related to the implementation of cloud-based AIS, its challenges, and its impact on efficiency and sustainable business practices. Through a descriptive literature study approach, it is found that the adoption of cloud-based AIS can reduce operational costs, enhance the accuracy of financial reporting, and facilitate realtime data access. Digital business entities still face several critical challenges, such as cybersecurity issues, inadequate digital infrastructure, and limited digital literacy and capabilities of human resources in managing technology-based systems. The transformation toward cloud-based AIS also supports sustainability practices by reducing the need for physical infrastructure and increasing transparency in reporting. The findings of this review are expected to serve as a strategic foundation for companies planning to optimize cloud technology to enhance operational efficiency and ensure business sustainability